1982
DOI: 10.1002/1097-0142(19820201)49:3<547::aid-cncr2820490325>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Malignant interstitial cell tumor of the testis

Abstract: A case of malignant interstitial cell tumor of the testis is reported and the literature is reviewed. Malignant interstitial cell tumors occur exclusively in adults. Gynecomastia was noted in 12% of the cases. Elevated plasma levels or increased urinary excretion of estrogen, 17-ketosteroid, or testosterone were demonstrated in 64% of the patients. Vessel invasion, which occurred in 74% of the patients, appears to be the only reliable histologic feature for predicting malignant behavior. There is no proved sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 21 publications
1
5
0
2
Order By: Relevance
“…However, Chen et al have reported that malignant tumors can be identified by the histologic appearance of the primary tumors. They had described malignant interstitial cell tumors with histological features of vessel invasion and capsular invasion [4]. Our case had these histological features, with capsular invasion.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, Chen et al have reported that malignant tumors can be identified by the histologic appearance of the primary tumors. They had described malignant interstitial cell tumors with histological features of vessel invasion and capsular invasion [4]. Our case had these histological features, with capsular invasion.…”
Section: Discussionsupporting
confidence: 60%
“…Microscopic criteria suggestive of malignancy in the tumor included: (1) marked cellular pleomorphism with bizarre cell forms and atypical nuclei; (2) numerous and atypical mitoses; (3) invasion of vascular or lymphatic channels; (4) extension of the tumor into the spermatic cord and invasion of the capsule [4][5][6][7] (see Figure 1). …”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of Sertoli cell tumors has been reported as follows. Patients with pathologically benign tumor showed neither recurrence nor metastasis if the tumor was completely removed, whereas approximately half the patients with malignant tumor died of metastasis 1–3 . It is therefore important to diagnose and treat this condition correctly.…”
Section: Discussionmentioning
confidence: 99%
“…30% der Er-wachsenen zeigen endokrinologische Auffälligkeiten mit erhöhtem Östrogen, vermindertem LH und FSH, sowie eine gestörte Spermiogenese (12,13,17,18,19), deren Abklärung auch bei unseren beiden Patienten zur Diagnose des Hodentumors führte. CEA, ß-HCG und Alpha-Fetoprotein sind in der Regel nicht erhöht (4,19 Sowohl die Patienten mit nichtseminomatösen Keimzelltumoren, als auch die Patienten mit malignen nicht germinalen Hodentumoren werden nach der operativen Therapie in ein engmaschiges Nachsorgeprogramm übernommen, in dem eine Sonographie des Abdomens, körperliche Untersuchung, Markerkontrolle und Rö-Thorax in a /jährlichen, ein CT des Abdomens und bei Sertoli-und Leydigzelltumoren Knochenszintigramm in V2Jährlichen Abständen durchgeführt werden (Tab. 1) (12,17,18,19).…”
Section: Leydigzelltumorenunclassified
“…Eine Radiatio führt offenbar zu keiner Tumorverkleinerung (13). Bei isolierter retroperitonealer Metastasierung wird eine radikale retroperitoneale Lymphadenektomie dringend angeraten (4). Es scheint, daß die radikale operative Behandlung derzeit die besten Ergebnisse erzielt.…”
Section: Leydigzelltumorenunclassified